Advances in the study of behavior. (Advances in the study of behavior, 2003)
The aim of Advances in the Study of Behavior remains as it has been since the series began: to serve the increasing number of scientists who are engaged in the study of animal behavior by presenting their theoretical ideas and research to their colleagues and to those in neighboring fields. We hope that the series will continue its "contribution to the development of the field", as its intended role was phrased in the Preface to the first volume in 1965. Since that time, traditional areas of animal behavior have achieved new vigor by the links they have formed with related fields and by the closer relationship that now exists between those studying animal and human subjects.